Money and coinage in the Middle Ages - Naismith, Rory (Reading medieval sources, 2018)
"This volume is about ways of studying medieval money, and especially the most direct manifestation of money: coinage. It is intended to introduce readers to a range of approaches to a subject that has traditionally been seen as somewhat specialized; a domain of highly technical study which often seems to sit at some remove from the mainstream of historical and archaeological research. One important aim of the chapters offered here is to show ways in which money can be incorporated into analysis of the Middle Ages more broadly"--